Особливості культурогенезу на території Північно-Західної України у першій половині І тис. н. е. (за матеріалами пам’яток липицького типу) - Козак, Д.Н. (Археологія, 1990)
У статті на підставі нової теоретичної бази переглядається культурна та етнічна атрибуція пам’яток, відомих в літературі як липицька культура. Автор доходить висновку, що липицькі пам’ятки не можуть бути об’єднані поняттям «археологічна культура». Вони ілюструють характерне лише для контактної зони культурне явище, що може називатися «культурною групою». Еволюція пам’яток лцпицької культурної групи відбиває, на думку автора, процес асиміляції праслов’янами у І—ІІ ст. дакійського субстрату. В статье на основании многочисленных археологических источников и теоретических разработок рассматриваются некоторые особенности этно-культурного развития на территории Северо-Западной Украины в первых веках н. э. Указанные земли были одной из наиболее активных контактных зон Европы, которые характеризуются своеобразием исторического процесса. Устанавливаются основные черты этно-культурного развития в контактной зоне, вводятся новые понятия: «культурная группа» (КГ), «культурно-этнический тип» (КЭТ). Теоретические положения рассматриваются на примере памятников, известных в литературе под названием «липицкая культура». Автор приходит к выводу, что липицкие памятники не соответствуют общепринятому понятию «археологическая культура». Они иллюстрируют наличие другого, характерного лишь для контактной зоны, культурного явления — «культурной группы». Эволюция памятников липицкой культурной группы отражает процесс ассимиляции праславянами дакийского субстрата в I—II вв. н. э. Using vast archeological material and theoretical investiqations the author analyzes some special features of ethnic-cultural development in the territory of the North-Western Ukraine in the first centuries A. D. This area is considered to be one of the most active zones of ethnic and cultural contacts in Europe. And this fact can explain the peculiarities of the historical process. The author attempts to specify the main features of the ethnic-cultural development in the contact zone with the new categories «cultural group» and «cultural-ethnic type». The theoretical statements are considered through relics known in literature as «Lipitsa culture». The author comes to a conclusion that the Lipitsa records do not correspond to the generally acknowledged term «archeological culture». They illustrate the availability of another cultural phenomenon — «cultural group» — which is typical only of the contact zone. The evolution of antiques of the Lipitsa cultural group reflects the process of assimilation of Dacian elements by Protoslavs in the lst-2nd centuries A. D.